Hepatoprotective effects of parsley (Petroselinum Crispum) extract in rats with bile duct ligation - ÖZBEYLİ, DİLEK; ERCAN, FERİHA; YÜKSEL, MERAL (My University, 2022)
© 2022 Pan-Arab Association of GastroenterologyBackground and study aims: This study aimed to investigate the possible protective effects of parsley extract (Petroselinum Crispum; PC) against oxidative liver damage caused by bile obstruction in rats. Material and methods: Bile duct ligation (BDL) method was used to induce liver injury in rats. The rats were divided into the three groups each consisting of 8 rats; Sham-operated control (C), bile duct ligated + saline treated (BDL), and BDL + PC treated groups. PC extract was given at a dose of 2 g/kg orally for 28 days. Aspartate amino transferase (AST), alanin amino transferase (ALT), and bilirubin levels were analyzed in sera. In order to determine free radicals in liver injury, luminol and lucigenin chemiluminescence tests used. Oxidative stress was evaluated through superoxide dismutase, glutathione, malondialdehyde, Na+/K+-ATPase and 8-hydroxy guanosine levels. Furthermore, inflammation marker myeloperoxidase, apoptosis marker caspase-3, and fibrosis markers TGF- β and hydoxyproline were investigated. The liver tissues were also examined for histological evaluations. Results: While PC treatment decreased AST and ALT levels which increased with BDL, oxidant damage parameters also decreased with this treatment. Conclusion: The present study, which is the first research for PC extract on cholestasis induced liver damage, demonstrated that PC extract could be a potential therapeutic agent against liver fibrosis and need further studies.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Gastroenteroloji-(Hepatoloji); Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Gastroenterology and Hepatology; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GASTROENTEROLOJİ VE HEPATOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GASTROENTEROLOGY & HEPATOLOGY; Gastroenteroloji; Gastroenterology; Apoptosis; Cholestasis; Fibrosis; Oxidant damage; Parsley